KEBIJAKAN STRUKTUR MODAL, KEBIJAKAN DIVIDEN DAN NILAI PERUSAHAAN BANK BNI - Zainal Arifin Bambang Pamungkas (JOURNAL ECONOMICS AND STRATEGY, 2021)
This research is about “Capital structure policy, dividend policy and company value of BNI Bank with quantitative method. The financial statements of Bank BNI during its existence until now have been used as the population, sampling using the quota sampling technique with the results of the 2001-2020 financial statements, analyzed using multiple linear regression processed with Eviews 9. It was found that the multiple linear regression equation EPS = 730.81 + 1, 32 DER – 0.52 DPR. (F-statistics) is worth 0.008971 <0.05, which means simultaneously debt (DER) and dividends (DPR) significantly affect firm value (EPS). However, individually, only debt has a significant effect on firm value, this situation is indicated by the prob DER of 0.0070 <0.05. While dividends have no effect on the value of the company with a prob DPR value of 0.7193 > 0.05. Meanwhile, only 42.57% of debt and dividends contributed to the firm's value while the remaining 57.43% were other influences.